2019
DOI: 10.3390/coatings10010024
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of the Ti–6Al–4V Alloy in Sulfate-Reducing Bacteria Solution

Abstract: The corrosion behavior of the Ti-6Al-4V alloy was investigated in a sulfate-reducing bacteria (SRB) solution. The results showed that sulfate-reducing bacteria has good affinity with the surface of the Ti-6Al-4V alloy after 5 days. A potentiodynamic polarization test demonstrated that the corrosion resistance of the Ti-6Al-4V alloy was initially improved but deteriorated quickly in the subsequent period. The corrosion mechanism of the Ti-6Al-4V alloy was revealed by analyzing its microstructure with the aid of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…These latter results suggested that the bacteria had entered the stationary phase and that the biofilm on the surface of the alloy had matured. Similar results were reported by Zheng et al [53] in a study that was carried out with sulfate-reducing bacteria; similar to our results, this group reported an increase in R ct at the beginning of the monitoring period followed by a progressive decline at the end of the experiment. Similar behaviour was reported by Calvillo and Galicia [16], who presented impedance diagrams that illustrate times for adherence and attachment of Shewanella sp.…”
Section: Resultssupporting
confidence: 93%
“…These latter results suggested that the bacteria had entered the stationary phase and that the biofilm on the surface of the alloy had matured. Similar results were reported by Zheng et al [53] in a study that was carried out with sulfate-reducing bacteria; similar to our results, this group reported an increase in R ct at the beginning of the monitoring period followed by a progressive decline at the end of the experiment. Similar behaviour was reported by Calvillo and Galicia [16], who presented impedance diagrams that illustrate times for adherence and attachment of Shewanella sp.…”
Section: Resultssupporting
confidence: 93%
“…They found that the initiation and propagation of SRB-induced pitting corrosion was attributed to the generation of titanium sulfide located in micropits. Zheng et al also indicated that the presence of sulfur accelerated the breakdown of the passive film on Ti-6Al-4V, when exposed to an SRB-containing medium. Yang et al reported the passivation properties of Ti alloys in seawater containing sulfides and suggested that when the sulfide concentration in simulated seawater is greater than 2 mM, the protective capability of the passive film is significantly reduced because of an increase in corrosion productions such as TiOS and TiS 2 .…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, it is widely used in marine engineering equipment such as marine oil and gas exploitation, shipbuilding, nuclear power engineering, seawater desalination equipment, etc . However, in the metabolic process of anaerobic sulfate reducing bacteria (SRB) and the industrial process containing reductive sulfide, the integrity of the titanium passive film may be damaged and cannot be recovered quickly, which poses a major threat to the structural durability of titanium-based equipment.…”
Section: Introductionmentioning
confidence: 99%